2024
DOI: 10.1159/000538031
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor metalloproteinase-2 (TIMP-2) • IGF-binding protein 7 (IGFBP7) for the prediction of acute kidney injury following cardiac surgery

Yun Xie,
Qin Guo,
Bo Yang
et al.

Abstract: Introduction: Cardiac surgery-associated acute kidney injury (CSA-AKI) is a common complication associated with increased morbidity and mortality. Tissue inhibitor metalloproteinases-2 • insulin-like growth factor-binding protein 7 (TIMP-2•IGFBP7) determines tubular stress markers, which may occur prior to tubular damage. Previous studies on the use of TIMP-2•IGFBP7 for the prediction of CSA-AKI showed divergent results. Therefore, this study aimed to explore the predictive value of TIMP-2•IGFBP7 measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Despite the positive results, clinical outcomes vary, and other factors such as prior health problems and concurrent illnesses can have an impact on diagnosis accuracy. Combining [TIMP-2] × [IGFBP-7] with other clinical risk scores, such as SRI or EuroSCORE II, improves its predictive performance [58]. In another trial, nine percent of the 230 patients who had undergone cardiac surgery developed AKI.…”
Section: Acute Kidney Injury After Cardiac Arrest and After Cardiac S...mentioning
confidence: 99%
“…Despite the positive results, clinical outcomes vary, and other factors such as prior health problems and concurrent illnesses can have an impact on diagnosis accuracy. Combining [TIMP-2] × [IGFBP-7] with other clinical risk scores, such as SRI or EuroSCORE II, improves its predictive performance [58]. In another trial, nine percent of the 230 patients who had undergone cardiac surgery developed AKI.…”
Section: Acute Kidney Injury After Cardiac Arrest and After Cardiac S...mentioning
confidence: 99%
“…Tissue inhibitor metalloproteinase-2·insulin-like growth factor-binding protein 7 (TIMP-2·IGFBP7) are markers of renal tubular stress, potentially detectable before the onset of tubular damage. It has been reported that the postoperative use of TIMP-2·IGFBP7 enhanced the prediction accuracy of CSA-AKI and could assist in identifying patients at risk of short-term adverse outcomes ( 8 ). Another study reported that urinary C-C motif chemokine ligand 14 (CCL14), a newly discovered biomarker for persistent acute kidney injury (AKI), may help improve the clinical management of AKI patients ( 9 ).…”
Section: Introductionmentioning
confidence: 99%